Сравнение классического и пролонгированного режимов использования гормональной контрацепции у женщин с избыточной массой тела - Гридина, И. Б.; Круть, Ю. Я.; Авраменко, Н. В.; Грідіна, Ірина Борисівна; Круть, Юрій Якович; Авраменко, Наталія Вікторівна; Gridina, I. B.; Krut, Yu. Ya.; Avramenko, N. V. (Запоріжжя, 2016)
Сохранение репродуктивного здоровья и решение проблемы гиперандрогении у женщин с избыточной массой тела является актуальной проблемой нашего времени и признано важным направлением современной медицины. Цель исследования. Определить наилучший режим использования гормональной контрацепции для женщин с избыточной массой тела и гиперандрогенией. Материалы и методы. У 90 женщин с избыточной массой тела и гипе-рандрогенией изучена частота побоч¬ных эффектов и переносимость разных режимов использования гормональной контрацепции. Comparison of classic and extended modes use hormonal contraception in women with overweight The preservation of reproductive health in women with overweight and hyperandrogenia is an urgent problem of our time and is recognized as an important area of modern medicine. Aim. To determine the best mode use of hormonal contraceptive for women with overweight and hyperandrogenia. Methods and results. In 90 women with excessive body weight and hyperandrogenia studied the fre-quency of side effects of different modes use of hormonal contraception. Found that extended mode is most suitable for women with excessive body weight and hyperandrogenia compared to the classic mode use of hormonal contraception.
Comparison of classic and extented modes use hormonal contraception in women with overweight
Порівняння класичного та пролонгованого режимів застосування гормональної контрацепції у жінок з надмірною масою тіла
Keywords: контрацепция; избыточная масса тела; побочные реакции; гиперандрогения; contraception; overweight; side effects; hyperandrogenia